A self-organized experience in school physical education in a secondary school - Antunes, Alan Rodrigo; Betti, Mauro [UNESP] (Universidade Federal do Rio Grande do Sul, 2020)
This research aims to describe and understand the results of an intervention in Physical Education’s teaching and learning processes in a self-organized proposal based on Michel Debrun’s Theory of Self-Organization. It is an action research study guided by two main questions: Why and for what purpose do students are mobilized or not by contents presented to them? What are the attractors and noise and what roles do they play in teaching and learning processes? The study involved 16 students of the 5th period in a federal secondary-level vocational school. In this scenario, the results of the investigation pointed to the emergence of mobilization as attractors and noises appeared in the teaching and learning process.
Una experiencia autorganizada en educación física escolar en una escuela de nivel medio
Uma vivência auto-organizada na educação física escolar em uma escola de nível médio
Keywords: Education primary and Secondary; Learning; Physical Education